'The cooling of hearts': community truth-telling in Northern Uganda - Anyeko, Ketty (Human rights review, 2012)
Recent national and international debates on truth and reconciliation in Uganda have emphasized the importance of incorporating local-level mechanisms into a national transitional justice strategy. The Juba Peace Talks represented an opportunity to develop and articulate sufficient and just alternatives and complementary mechanisms to the international criminal model. The most commonly debated mechanism is the Acholi process known as mato oput (drinking the bitter root), a restorative justice approach to murder. Drawing on 2 months of research in nine internally displaced persons’ camps in 2007, we examine local justice practices in the region of northern Uganda to consider their potential, promise and pitfalls to realizing a successful truth-telling process. We find that although local mechanisms could help facilitate reconciliation in the region, truth-telling is but one part of a conciliatory process complicated by a national context of fear and the complexity of the victim–perpetrator identity at the community level. These locally informed insights help move forward the debate on such mechanisms in Uganda and add useful insights into community processes in the field of transitional justice more generally.